Internally Heated Convection and Rayleigh-Bénard Convection - Goluskin, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This Brief describes six basic models of buoyancy-driven convection in a fluid layer: three configurations of internally heated convection and three configurations of Rayleigh-Bénard convection. The author discusses the main quantities that characterize heat transport in each model, along with the constraints on these quantities. This presentation is the first to place the various models in a unified framework, and similarities and differences between the cases are highlighted. Necessary and sufficient conditions for convective motion are given. For the internally heated cases only, parameter-dependent lower bounds on the mean fluid temperature are proven, and results of past simulations and laboratory experiments are summarized and reanalyzed. The author poses several open questions for future study.
A Family of Convective Models -- Stabilities and Bounds -- Experiments and Simulations on Internally Heated Convection.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluid mechanics; Engineering Thermodynamics, Heat and Mass Transfer; Engineering Fluid Dynamics; Thermodynamics